Proposed standards for professional health sciences library services in hospitals of New York State. - Hutchinson, A P (1981)
Hospital libraries are considered to be the basic unit of the medical information system. A major statewide effort was begun in 1978 to introduce and support legislation in the New York State Legislature which would encourage hospitals to establish and maintain libraries that meet minimum services standards. Included in this legislation is the concept that the Commissioner of Education in consultation with the Commissioner of Health shall have the power to establish standards for hospital libraries. The Ad Hoc Committee for the Promotion of Hospital Library Services, Western New York Library Resources Council, proposes The Standards for Professional Health Sciences Library Services in Hospitals of New York State to clarify and to strengthen existing hospital library standards. These standards differ specifically from the Joint Commission on Accreditation of Hospitals standards in that they place equal and specific emphasis on eleven points: administration, qualifications of library staff, continuing education of library staff, requirement for a library advisory committee, required library services, required library resources, library space requirements, library budget, library network and consortium membership, documentation of library policy, and continued evaluation of the needs of the hospital for library service. Detailed interpretations are provided. An appendix describes the qualifications of a hospital library consultant.